Efeitos da cafeína sobre a memória de saguis (Callithrix jacchus) - Santana, Kathiane dos Santos (2009)
Caffeine is considered the most consumed psychostimulant in the world, presenting several central and peripheral effects. In the Central Nervous System the major effect occur by its antagonistic activity at the A1 and A2a subtypes of the adenosine receptors. These receptors are responsible for the slow-wave sleep induction, and their binding, caused by the consumption of foods and beverages that contain caffeine, cause behaviors like increase of alertness, mood and locomotion. The effects of caffeine on memory are still discussed because of the diversity of experimental protocols. Also, it does not have the same effects on all stages of the processing of memory - acquisition, consolidation and recall. Thus, using the marmoset (Callitrhix jacchus) as subject, we aim to evaluate the effects of caffeine on the memory of this primate through the conditioned place preference paradigm, where the animal selects a context by presence of food. This cognitive task consists of five phases. The first phase was two sessions of pre-exposure, in which they were evaluated for preference for any compartment of the apparatus. Then, we proceeded the training, conditioning the animals to the food-present context for 8 days. Then, there was administration of caffeine or placebo (10mg/kg) for 8 consecutive days, during the pre-sleep phase, where the 20 animals were distributed in two groups: placebo and repeated. The forth phase was one day of retraining, a re-exposure of the apparatus to the marmosets followed by the administration of caffeine (for the repeated group and a new group called abstinence) or placebo (for placebo and abstinence groups). Finally, was the test where we evaluated if the subjects learned where the food was present. Moreover, in this work we evaluate the existence of differences between females and males on the task, and the locomotor activity for the experimental groups. The results showed that in the pre-exposure phase the animals were habituated on the apparatus and did not present differences for any contexts. In training, they were able to learn the conditioning task, independent of gender. For the retraining, the two groups exhibited more interactions in rewarded context than that in non-rewarded context. Nevertheless, in the locomotor activity, the repeated group moved similarly in contact with the apparatus and outside of it. In the other hand, the animals of the placebo group moved more when in contact with the apparatus. In the test phase, the marmosets under influence of caffeine presented an increase in the locomotor activity when compared with the placebo group, corroborating works that show this increase in locomotion. In the learning evaluation, the continuous and abstinence groups had a bad performance in the task in relation to the placebo and acute groups. This suggests that the prolonged administration of caffeine disrupts the memories because it affected sleep, which is largely responsible offline processing of memories